Over at College : A Texas A&M Campus Kid in the 1930s - Walker, James Knox, Jr., 1927- (Book collections on Project MUSE., 2016)
In 1926 James Knox Walker, staff civil engineer in charge of building at A & M, and his new bride moved onto the campus of what was then known as the Agricultural and Mechanical College of Texas. The greater community, of which this small on-campus neighborhood was a part, was known simply as "College." There was no such place as College Station, and the city of Bryan stood six miles away. James Knox Walker Jr., the couple's oldest child, recollects the days when professors, staff members, and their children formed a small, closely knit society "over at College." The campus served as the childre